Geografske zasnove sonaravnega razvoja in samooskrbe Slovenije - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
To overcome the crisis, both on global and regional levels, does not mean to continue the traditional developmental practice but to implement a sustainable development concept. In Slovenia, it should be implemented in the country as a whole and in all its individual regions in order to pursue the welfare of the citizens of the present and future generations and also to balance economic, social and environmental development. Slovenia has all the essential developmental-protective geographical potentials (environmental resources) that are necessary for its transition to sustainable development, sustainable reinvigoration of economy and a safe degree of food and energy levels for its self-supply.
Keywords: environmental protection; Slovenia; Slovenija; sustainable development; trajnostni razvoj; varstvo okolja